Metropolis, money and markets Brazilian urban financialization in times of re-emerging global finance - Klink, Jeroen Johannes (Global urban studies, 2020)
"This book explores the impact of finance on urban spaces as well as cities' role in the social constitution and dissemination of financial logics and techniques. It brings together literatures from different disciplinary areas to increase our understanding of financialization. It observes how non-financial members of society, such as public bureaucrats, urban planners, the media, etc., are actively involved in the financialization of urban areas. With an explicit focus on Brazil, a developing country in the Global south, the book demonstrates how the country has been grappling with complex and contradictory processes of neoliberalization, decentralization, re-democratization and institutional-legal strengthening of frameworks for urban and regional planning, stressing the relations between urban space and finance capital. With a distinct view of filling a gap in the current literature on urban financialization, the book aims to focus on less developed areas in this field and link it with the literature on social studies of finance. This makes the text relevant for academics and scholars of urban studies and planning theory, geography, development studies and political economy, as well as scholars in the US and Europe interested in understanding Brazilian patterns of financialization"--